Thesaurus of craft and professional terminology in Ukrainian bibliopegy: the issues of a special dictionary formation - Halchenko O. (Рукописна та книжкова спадщина України, 2015)

(untitled)
The article covers terminological problems which arise when medieval manuscripts’ bindings are described for scientific catalogs and electronic databases. The author attempts to analyze the causes of these problems and ways to overcome them. Reviewed are handwritten and printed sources, which contain the terms dealing with manuscripts production, and substantiated is the relevance of formation of the national craft and professional terminology thesaurus in Ukrainian codicology and bibliopegy. We have also defined the basic steps of the dictionary creation, which are the following: collecting special terms and creating a glossary and card index; translation, editing and unification of borrowed terms; creation of a digital visual dictionary